Analisis Konvergensi Fikih-Medis pada Khitan Laki-Laki dan Divergensi pada Female Genital Mutilation/Cutting (FGM/C) - Fauzi, Irfan; Lubis, Yeni Amalia; Mariadi, Ahmad Mahrus; Rahman, Riski Taufikur (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
The conflation of male circumcision and female genital mutilation/cutting (FGM/C) in public discourse has created a complex nexus of overlapping cultural, religious, and health norms. This research aims to critically and comparatively analyze both practices to delineate their fundamental distinctions. Employing a qualitative literature review of primary (jurisprudence, fatwas, law) and secondary sources (scholarly journals, reports), the findings reveal a sharp divergence. Male circumcision demonstrates a positive convergence between Islamic jurisprudence (fiqh) and medical evidence. Conversely, FGM/C reveals a dual contestation: an internal jurisprudential debate between classical and contemporary scholars over the interpretation of religious texts, and a policy-level conflict where a permissive MUI (Indonesian Ulema Council) fatwa clashes with the global medical consensus and prohibitive national law. In conclusion, the two practices are fundamentally different. Therefore, this study recommends that the government adopts the WHO’s definition of FGM/C into a binding national regulatory framework, thereby creating a single, authoritative standard across all policy sectors to protect the health rights and bodily integrity of women and children.